PHOTON-PARTICLE , PHOTON-WAVE OR DUALITY - PHOTON ? - Giorgallides, Marcos (IJRDO-Journal of Applied Science, 2020)
Distance is the Quantum of E-Geometry, while Material-point is the Quantum in Physics and Material-Geometry which is the composition of opposites and are the Elements in Chemistry and Physics . As in Algebra Zero ,0, is the Master-key number for all Positive and Negative numbers , because their sum and multiplication is zero , and the same on coordinate-system ± axes pass from zero , The Rolling of Positive ⊕ , constituent on the Negative ⊝ , constituent , creates the Neutral Material point which Equilibrium . Spin